Miami Vice : Season 1 Disc 3 Episodes 1-11 - Leither, Stan.; Johnson, Don. (Universal Studios USA, 1984)
To hear the opening beats of Jan Hammer's percussive, propulsive Miami Vice theme is to be instantly transported back to 1984. But this groundbreaking series, with its cinematic sensibility, cool clothes, and killer soundtrack is no mere blast from the past. It still rocks. This three-disc set would be worthless if it didn't. Music was an integral part of Miami Vice's hip vibe. The soundtrack propelled the stories and established the mood like no series before it. So the first thing you want to know is: Have the music rights been secured for this DVD release? In the pilot episode, does Phil Collins's "In the Air Tonight" still play ominously as vice undercover cops Crockett and Tubbs speed toward a bust? Does Eric Clapton's "Wonderful Tonight" serenade Sonny and Gina on his boat in the episode "One-Eyed Jack?" And what would the benchmark episode, "Smuggler's Blues" be without Glenn Frey's instant classic? From the Rolling Stones on a boombox to Elvis Presley singing "Rubberneckin'" on a TV, Vice's cutting-edge soundtrack has been preserved and honed in 5.1 surround sound glory.Miami Vice made stars out of Don Johnson, Philip Michael Thomas, and Edward James Olmos, who won an Emmy as the intense, taciturn Lt. Castillo (watching him bust some martial arts moves in "Golden Triangle" is like Yoda cutting lose in Attack of the Clones), but the first season also offers time-capsule glimpses of actors on the cusp of stardom, including a pre-L.A. Law Jimmy Smits in the pilot, a pre-Crime Story Dennis Farina in "One-Eyed Jack," and a pre-Moonlighting Bruce Willis in "No Exit." Miami Vice put a neon sheen on cop-show convention. Its fashion sense (pastel suits, no belt, no socks), and the brilliantly employed freeze frames are still arresting. Miami Vice was a TV watershed, and this DVD set does it full justice.
The cops. The cars. The clothes. From executive producer Michael Mann (Heat, Collateral) comes the first season of the explosive, groundbreaking detective show that redefined the word cool. Set against the seamy and steamy Miami underworld, ride shotgun with suave Vice cops Sonny Crockett (Golden Globe winner Don Johnson) and Rico Tubbs (Philip Michael Thomas) as they battle a never-ending gallery of criminals, drug dealers and lowlifes. Set to Jan Hammer s electrifying score and featuring a soundtrack of rock legends, including Glenn Frey, Phil Collins, U2 and Peter Gabriel, every episode crackles with excitement and stylish flair. Also starring Emmy and Golden Globe winner Edward James Olmos and a powerhouse roster of guest stars including Ving Rhames, Jimmy Smits and Bruce Willis. See why Time magazine called Miami Vice TV s hottest and hippest cop show.
Language: English Subtitle: Turkish
Keywords: Action -- Adventure -- Crime -- Thriller -- Drama; TV Series